Block periodization training of endurance athletes: A theoretical approach based on molecular biology - Goutianos, G. (Cellular and Molecular Exercise Physiology, 2016)
Competitive endurance athletes are constantly looking for ways to maximize training adaptations and to push their performance to the limit. A fundamental feature of their training is the subdivision of the annual training plan into shorter periods (periodization of training). Block periodization has been proposed as an alternative training organization that could be incorporated into the annual training plan. Despite the plethora of studies investigating exercise induced adaptation in response to differing intensities of endurance exercise and following various feeding strategies, only a limited number of studies have examined the effect of different BP programs on adaption and performance in endurance exercise. Although these studies found increased adaptations in response to BP compared to traditional organisation models they do not currently provide an insight into the underpinning mechanisms. This review presents the current advances in the molecular biology underpinning adaptation to exercise and how this evidence may be used to understand BP training and therefore provides future recommendations into annual training organization. This approach involves discussion of several issues related to BP: A discussion on whether monotony of training blunts molecular responses to exercise, if periodization of training alters myocellular responses to endurance training and finally the addition of strength training to BP. The author also discusses new research findings supporting the existence of skeletal muscle `memory` and compares this evidence to findings that highlight the importance of maintenance sessions and/or manipulation strategies of muscle glycogen concentration during BP training. Finally, based on the current evidence, the author recommends strategies to maximize adaptation to training in response to BP in competitive endurance athletes.